(3GdQSGdI GdeSJWQaI dHjGf eTghQ cJH GdSfI GdeTQaI heG jJHYgG ef cJH GdhSGFd GdJi JHJZi ddbGUO hGdSGFds - (3eMeO Hf LYaQ GdcfGfj,J (B1345 (3g` s ((3MeRI Hf GdYQHi GdJbQJi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi fRd CMSf GdMOjK cJGHkG , hGdSdGe Ydi ef LGA HHjGf eG CfRd Edjg SchJkG haYdkG hNWGHkG s
(3BNQgG (B:s
(3hjLYdfG ef GdeJWadjf Ydi CHhGH gPG GdfHi GdcQje , hNOGe MVQJg GdYdjI hBNQ OYhGfG Cf GdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HChdg Jedc HGSe GdTjN YeQ MeOGfs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs